2016
DOI: 10.3390/md14040077
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Guanidine Alkaloids from Poecilosclerida Marine Sponges

Abstract: Sessile marine sponges provide an abundance of unique and diversified scaffolds. In particular, marine guanidine alkaloids display a very wide range of biological applications. A large number of cyclic guanidine alkaloids, including crambines, crambescins, crambescidins, batzelladines or netamins have been isolated from Poecilosclerida marine sponges. In this review, we will explore the chemodiversity of tri- and pentacyclic guanidine alkaloids. NMR and MS data tools will also be provided, and an overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…C800 is a guanidine alkaloid isolated mostly from sponges such as Crambe crambe [ 34 , 36 , 37 ] and Monanchora sp [ 38 , 39 ] and has been demonstrated to have diverse biological activities [ 38 , 40 ]. It has been found that C800 induces erythroid differentiation in chronic leukemia cells (K562 cells), leading to cell cycle arrest at S-phase and promotes neurite outgrowth in Neuro-2A neuroblastoma cells [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…C800 is a guanidine alkaloid isolated mostly from sponges such as Crambe crambe [ 34 , 36 , 37 ] and Monanchora sp [ 38 , 39 ] and has been demonstrated to have diverse biological activities [ 38 , 40 ]. It has been found that C800 induces erythroid differentiation in chronic leukemia cells (K562 cells), leading to cell cycle arrest at S-phase and promotes neurite outgrowth in Neuro-2A neuroblastoma cells [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crambescidins, batzelladines, mirabilins and ptilocaulins are definite groups of marine cyclic guanidine-containing alkaloids that display potent biological activities, such as cytotoxic, antiviral, antifungal and anti-HIV-1 gp 120-human. These compounds were isolated from various marine sponge genera, like Batzella , Crambe , Monanchora and Ptilocaulis , and are chemotaxonomic markers for the marine sponges belonging to the orders Poecilosclerida and Axinellida [ 22 , 27 ]. Crambescidin 800 ( 1 ), a pentacyclic guanidine alkaloid, was isolated from the marine sponge Clathria ( Thalysias ) cervicornis , and was found to display potent antimicrobial activity against Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa , with MIC values of 2, 1 and 1 μg/mL, respectively [ 21 ].…”
Section: Chemistry and Biological Activities Of The Secondary Metamentioning
confidence: 99%
“…Monanchora , of the order Poecilosclerida and the family Crambeidae, is one of the richest sources of MGAs, especially complex polycyclic guanidines, such as crambescidins, ptilomycalins, fromiamycalins, celeromycalins, batzelladines, monanchomycalins, monanchocidins, normonanchocidins, neofolitispates, etc. Most of the recently reported MGAs were derived from this genus, with a wide range of biological activities such as cytotoxic, antimicrobial, antimalarial, and anti-HIV properties [ 12 ].…”
Section: Mgas From Spongesmentioning
confidence: 99%